THE IMPACT OF US ELECTIONS ON THE DOLLAR’S EXCHANGE RATE - Alexiou, Constantinos; Vogiazas, Sofoklis; Kane, Colston (Economic Annals, 2023)
This paper explores the effect of U.S. domestic politics on the behaviour of international currency markets. Specifically, for the first time in the literature, we gauge the impact of a divided government on the exchange rate volatility of five currencies: the Japanese yen, the Canadian dollar, the British pound, the Mexican peso, and the euro. At the same time, we control for the impact of political and macroeconomic factors. A GARCH methodology has been adopted for this objective, using weekly data from 2000 to 2021. The evidence suggests that the partisan and divided government variables significantly impact the conditional variance equation, whilst the observed reduced levels of exchange rate volatility during a Democrat presidency run counter to prior studies on partisanship. In addition, exchange rate volatility seems to increase one month before an election and during periods of divided government. Given the nascent evidence, we argue that U.S. politics are instrumental in affecting global financial markets.